The Effect of Psychosocial Approach Education on Diabetes Control in Patients with Diabetes Mellitus and Depression in Comprehensive Health Care Centers in Isfahan City, Iran, 2018-2019 - Mahmood Reza Zahednezhad; Zahra Dana Siadat; Zahra Amini (مجله دانشکده پزشکی اصفهان, 2019)
Background: The present study aimed to investigate the effect of psychosocial approach on depression and blood glucose control in patients with type 2 diabetes mellitus and depression.